A Severe Case of Median Arcuate Ligament Syndrome with Successful Angioplasty and Stenting - Keerati Hongsakul; Sorracha Rookkapan; Jitpreedee Sungsiri; Teeravut Tubtawee (Case Reports in Vascular Medicine)
Median arcuate ligament syndrome (MAL) or celiac axis compression syndrome (CACS) is a rare etiology of chronic abdominal pain. Traditional treatment of this syndrome is surgery. We report a case of median arcuate ligament syndrome with a severe compression of the celiac trunk, which was successfully treated by angioplasty with stenting.